The Effect of Financial Report Readability, Accounting Policy Consistency, Performance Reporting Pressure, And Information Asymmetry on the Earnings Quality of Public Companies - Mohammad Rizky Yahya; Juan Anastasia Putri; Muhammad Rispan Affandi; Ngurah Pandji Mertua Agung Durya; Merissa Fermica Iskandar Iskandar (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines the effect of financial report readability, accounting policy consistency, performance reporting pressure, and information asymmetry on the earnings quality of public companies. Earnings quality is a crucial indicator for investors and stakeholders because it reflects the extent to which reported earnings represent a firm’s true economic performance. Readable financial reports enhance transparency and reduce misunderstanding among users of financial statements. Accounting policy consistency ensures comparability and reliability of financial information across periods. Performance reporting pressure may encourage managerial opportunistic behavior, potentially reducing earnings quality. Meanwhile, information asymmetry arises when managers possess superior information compared to external stakeholders, which may increase earnings management practices. This study employs a quantitative research approach using secondary data obtained from publicly listed companies. The sample consists of 100 firm-year observations selected through purposive sampling. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS). The analytical techniques include descriptive statistics, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and hypothesis testing. The results indicate that financial report readability and accounting policy consistency have a positive and significant effect on earnings quality. Conversely, performance reporting pressure and information asymmetry have a negative and significant effect on earnings quality. Simultaneously, all independent variables significantly influence earnings quality. These findings suggest that improving transparency and consistency in financial reporting while reducing excessive performance pressure and information asymmetry can enhance the quality of corporate earnings. This study contributes to financial accounting literature and provides practical implications for regulators, managers, and investors.